2018
DOI: 10.1007/s12325-018-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

Unlicensed and Off-Label Medication Use in Pediatric and Neonatal Intensive Care Units: No Change Over a Decade

Abstract: The current study confirms the high prevalence of unlicensed and off-label drug use in a PICU and NICU setting. Compared with a similar study conducted in the same PICU in 2002, despite regulatory efforts conducted in this area, the prevalence of unlicensed medications was surprisingly higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 26 publications
3
24
0
17
Order By: Relevance
“…30,31 Öte yandan pediatrinin, EDİK'in yüksek görüldüğü alanların başında olduğu bilinmektedir. 6,32 ŞEKİL 2: Türkiye'de klinik araştırmalar ile ilgili atılan ve çocukları yakından ilgilendiren adımların kısa tarihçesi.…”
Section: çOcuklarda Endi̇kasyon Dişi İlaç Kullaniminin Dünyadaki̇ Günceunclassified
See 1 more Smart Citation
“…30,31 Öte yandan pediatrinin, EDİK'in yüksek görüldüğü alanların başında olduğu bilinmektedir. 6,32 ŞEKİL 2: Türkiye'de klinik araştırmalar ile ilgili atılan ve çocukları yakından ilgilendiren adımların kısa tarihçesi.…”
Section: çOcuklarda Endi̇kasyon Dişi İlaç Kullaniminin Dünyadaki̇ Günceunclassified
“…33,[35][36][37] Bu tespitler, çocuklarda EDİK'in yapılacak hedef popülasyona özgü çalışmalarla azaltılması ve/veya daha rasyonel hâle getirilmesi gereken bir halk sağlığı konusu olduğunu ortaya koymaktadır. 11,32,[38][39][40][41] Çocuklarda EDİK'i etkileyen faktörlerin iyi bilinmesi, uygulamanın rasyonel yönetilmesine katkı sağlayabilir. Yaş, çocuklarda EDİK oranını değiştiren kriterlerden biridir.…”
Section: çOcuklarda Endi̇kasyon Dişi İlaç Kullaniminin Dünyadaki̇ Günceunclassified
“…18 Off-label use of drugs presents an even larger and more complex issue in preterm and full-term neonates, in infants and children ages <2 years, in children with rare or chronic diseases, and in those who are critically ill. In fact, Nir-Neuman et al 19 reported that among the 1064 prescriptions for 49 medications in critically ill neonates, 64.8% involved off-label use. Likewise, the number of critically ill pediatric patients receiving at least 1 off-label medication was 88.7%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there has been an increase in the use of unlicensed and off‐label medication on inpatients (particularly neonates and inpatients in the paediatric intensive care unit). The propagation of preschool and neonates exposed to such medicine use is high …”
Section: Introductionmentioning
confidence: 99%